Association between physical activity and inflammatory bowel disease risk: A meta-analysis. Issue 12 (December 2016) - Wang, Qiang; Xu, Ke-Qun; Qin, Xiang-Rong; Wen-Lu; Yan-Liu; Wang, Xiao-Yong
Abstract: Background: Previous studies of an association between physical activity and inflammatory bowel disease have yielded conflicting results. Aim: This meta-analysis was conducted to clarify whether there is an association between physical activity and inflammatory bowel disease. Methods: The PubMed and Web of Science databases were searched for relevant studies published up to October 2015. Data were extracted and the summary relative risks (RRs) were calculated using a random effects or a fixed-effects model, according to heterogeneity. Results: Seven studies were included in the analysis. Relative to individuals with low physical activity, those who participated in high physical activity had an RR of 0.63 (95% CI, 0.50–0.79) for developing Crohn's disease. In stratified analyses, a significantly lower risk for Crohn's disease was associated with high physical activity in Europeans only (RR, 0.62; 95% CI, 0.43–0.91); population-based control studies (RR, 0.56; 95% CI, 0.41–0.76); and case-control studies (RR, 0.56; 95% CI, 0.41–0.75). The data of 6 studies were pooled to analyze the effect of physical activity on the risk of ulcerative colitis, and no significant association was found (RR, 0.82; 95% CI, 0.68–1.00). Conclusions: The pooled results of observational studies support that physical activity has a protective effect against Crohn's disease.